Does culture affect unemployment? Evidence from the Röstigraben - Beatrix Brügger; Rafael Lalive; Josef Zweimüller (Institute for the Study of Labor (IZA), 2009)
This paper studies the role of culture in shaping unemployment outcomes. The empirical analysis is based on local comparisons across a language barrier in Switzerland. This Röstigraben separates cultural groups, but neither labor markets nor political jurisdictions. Local contrasts across the language border identify the role of culture for unemployment. Our findings indicate that differences in culture explain differences in unemployment duration on the order of 20%. Moreover, we find that horizontal transmission of culture is more important than vertical transmission of culture and that culture is about as important as strong changes to the benefit duration.
urn:nbn:de:101:1-2009082156
Keywords: J21; J64; Z10; 330; Culture; cultural transmission; unemployment duration; regional unemployment; Arbeitslosigkeit; Dauer; Kulturpsychologie; Ethnopsychologie; Sozialer Wandel; Regionale Arbeitslosigkeit; Schweiz